Evaluation of the effects on atherosclerosis and antioxidant and antimicrobial activities of Agaricus xanthodermus poisonous mushroom - Özaltun, Betül; Sevindik, Mustafa (The European Research Journal, 2020)
Objectives: The aim of this study was to determine the total antioxidant capacity, total oxidant capacity, oxidative stress index and antimicrobial activity of a poisonous mushroom Agaricus xanthodermus. The effects of mushrooms on atherosclerosis are due to their antioxidant effects.Methods: Mushroom samples collected from study field were extracted with methanol (MeOH) and dichloromethane (DCM) using soxhlet apparatus. Total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) were measured using Rel Assay trade kits. Antimicrobial activities were tested on 9 microorganisms (Staphylococcus aureus, S. aureus MRSA, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, Candida albicans, C.krusei and C. glabrata) using the modified agar dilution method.Results: In this study A. xanthodermus has shown high antioxidant and antimicrobial activities. In addition, the highest activities of MeOH and DCM extracts of the mushrooms were demonstrated against E. coli, P. aeruginosa, and A. baumannii.Conclusions: In conclusion, A. xanthodermus is considered to be a poisonous mushroom and can be used as a pharmacological natural agent due to its high antioxidant and antimicrobial activities.